Evaluating the sustainable adoption potential of electric off-road vehicles in Malaysia’s agriculture sector - Mohd Din, Adilah; Abdullah, Mariam Miri; Othman, Azrina; Mohamad, Norhidayah; Yaacob, Ahmad Zaki (SHPMedia Sdn Bhd, 2025)
Malaysia’s agricultural sector, a key economic pillar, faces escalating challenges: labour shortages, high operational costs and mounting pressure for sustainable practices. This study explores the transformative potential of electric off-road vehicles (E-ORVs) in addressing these issues, with a focus on realising a future where agriculture is productive and environmentally responsible. Through a qualitative phenomenological approach combined with the technology acceptance model, semi-structured interviews were conducted with representatives from influential agricultural agencies. They revealed deep insights into the perceived benefits and barriers to E-ORV adoption. Findings indicate that stakeholders view E-ORVs as a solution to improve efficiency and reduce carbon footprints. However, adoption remains hindered by high costs, sparse rural infrastructure and technical concerns related to Malaysia’s tropical conditions. This study outlines a strategic framework for overcoming these barriers. It also recommends targeted financial incentives, rural infrastructure development and tailored awareness programmes to facilitate E-ORV integration. By addressing these challenges, Malaysia can spearhead a shift towards sustainable mechanisation, positioning its agricultural sector at the forefront of environmental innovation in Southeast Asia.